ChemInform Abstract: Modular Bipyridine Ligands Coupled with Cinchona Alkaloids for Cu(II)‐Catalyzed Asymmetric Henry Reactions. Issue 48 (26th November 2013) - Liu, Ming; Ma, Shijun; Tian, Zhiqing; Wu, Hao; Wu, Lulu; Xu, Xiufang; Huang, Yaodong; Wang, Yongmei
Abstract Novel bipyridine substituted cinchona ligands are prepared and successfully applied to Cu(II)‐catalyzed asymmetric Henry reactions.